Kemapanan Finansial Sebelum Menikah dan Relevansinya terhadap Kesiapan Pernikahan Generasi Milenial dalam Perspektif Maqāṣid al-Syarī‘ah - Dina Sahara Putri; Nurnazli; Novalia, Sisca (Kartika: Jurnal Studi Keislaman, 2026)
The phenomenon of delayed marriage among the millennial generation indicates a shift in values, particularly in interpreting financial stability as a primary prerequisite for marriage. This condition raises academic concern, as in the Islamic perspective, financial stability is not an absolute requirement but rather part of basic readiness. This study aims to analyze the concept of financial stability from the perspective of maqaṣid al-shari’ah and to examine millennials’ views on financial stability as a benchmark for marriage readiness. The research employs a field study with a descriptive qualitative approach using interviews, observations, and documentation techniques. The findings reveal that millennials perceive financial stability as the ability to have a stable income, manage finances wisely, and fulfill basic household needs. However, excessive emphasis on financial stability has the potential to lead to delayed marriage. From the perspective of maqaṣhid al-shari’ah, financial stability is understood as a supporting factor rather than a barrier. The implications of this study highlight the importance of a proportional understanding of marriage readiness, encompassing financial, spiritual, and social aspects in order to achieve a harmonious family characterized by sakinah, mawaddah, and warahmah